PENGHITUNGAN EMISI KARBON DARI LIMA SEKTOR PEMBANGUNAN BERDASAR METODE IPCC DENGAN VERIFIKASI FAKTOR EMISI DAN DATA AKTIVITAS LOKAL - Purwanta, Wahyu (Jurnal Teknologi Lingkungan, 2010)
After ratifying the Kyoto Protocol, Indonesia has obligation to make report on National GHGs emission for UNFCCC. There are some studies at national level related to GHGs inventory. In this study we calculated GHG (CO2 and CH4) emissions from 5 (five) sectors i.e forestry, energy, industry, agriculture and waste. Calculation use 2006 IPCC method with local values for verification or enhanced the Tier of method. The local values are, forestry allometric equation, emission factor of paddy field, generation and composition of municipal solid waste, solid waste management as well. Calculation result of GHGs emission in this study is 827,058 Gg/year in the term of CO2 equivalent. This numbers isestimated arround 60% of the realistic numbers due to the accuracy of the transportation data and unaccounted peat fire data in the study. Carbon emission from peat fire is the biggest emission. From all sector has calculated, forestry sector is the biggest CO2e emmitor with contribute arround 58%, follow energy sector (25%), agriculture (8% ),industry sector (6%), and waste sector (3%). The proportion of distribution each sector can change if the data more broad the calculation include more detail in sub sectors.Key words : GHGs Emissions, Local Values, Sector Contribution